Social Reform in Times of Transition. Reflections on Martin Conway’s The Sorrows of Belgium - Nico Wouters (BMGN: Low Countries Historical Review, 2014)
In his book The Sorrows of Belgium Martin Conway uses the Belgian case to look at the restoration of liberal parliamentary states in Europe between 1945 and 1947. Nico Wouters’ contribution focuses on three elements brought to the fore by Conway: 1) the essential yet ambivalent role played by local government (cities and municipalities), 2) the inability to institutionalise Belgian patriotism as binder for the nation-state and finally, 3) the rift between shifts in class relations and political institutional renewal. His contribution comments on each of these elements, by means of superficial comparisons with the Netherlands.